2005
DOI: 10.1590/s0103-50532005000700009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mercury contamination in sediments from Santos - São Vicente Estuarine System, São Paulo State, Brazil

Abstract: A distribuição da contaminação por mercúrio no sistema estuarino de Santos -São Vicente foi observada pela análise de 31 amostras de sedimentos coletadas desse sistema, incluindo as áreas de manguezais localizadas em zonas sob influência urbana, industrial e portuária. Os valores obtidos de Hg variaram de 0,04 a 1,19 μg g -1 , sendo que cerca de 90% das amostras apresentaram concentrações superiores a 0,13 μg g -1 , limite estabelecido pela legislação Canadense e adotado pela Companhia de Tecnologia e Saneamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
23

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 19 publications
(28 reference statements)
1
32
0
23
Order By: Relevance
“…To this end, 2 g of each sediment sample was weighed. Samples were mixed with 4 mL of aqua regia (3:1 HCl:HNO3), 1 mL of high-purity water and 1 mL of HClO4 in 50 mL beakers covered with watch glass and heated for 30 minutes at 90°C in a water bath by using the procedure of Hortellani et al (2005). After cooling, the samples were filtered through qualitative filter paper into volumetric flasks of 25 mL and the volume was made-up with ultrapure water.…”
Section: Sample Preparationmentioning
confidence: 99%
“…To this end, 2 g of each sediment sample was weighed. Samples were mixed with 4 mL of aqua regia (3:1 HCl:HNO3), 1 mL of high-purity water and 1 mL of HClO4 in 50 mL beakers covered with watch glass and heated for 30 minutes at 90°C in a water bath by using the procedure of Hortellani et al (2005). After cooling, the samples were filtered through qualitative filter paper into volumetric flasks of 25 mL and the volume was made-up with ultrapure water.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Since Hg sources are not known for the Piaçabuçu, Mariana and Santana Rivers (Lamparelli et al, 2001), the presence of this metal seems to depend not only on point sources (industrial complex and some port terminals), but also on diffuse sources. Indeed, Hortellani et al (2005; and Abessa et al (2008) suggested that the broad spatial distribution of Hg across the SSES may be due to multiple sources, such as the industrial effluents, landfills and atmospheric deposition.…”
Section: Comparison With Sediment Quality Guidelinesmentioning
confidence: 99%
“…This gradient of contamination from the inner to the outer portions of the SSES was previously reported (Lamparelli et al, 2001;Abessa et al, 2008;Torres et al, 2009). According to Hortellani et al (2005), besides the presence of metal sources, the inner portions of the SSES are also affected by tides restricting water circulation, which hinders the dispersion of the contaminants and their accumulation in the sediments.…”
Section: Comparison With Sediment Quality Guidelinesmentioning
confidence: 99%
“…e isentos em Hg, sob refluxo 15 , para se evitar perdas de elementos voláteis, como Zn e Hg. Pesou-se uma massa de 0,500 g de cada sedimento e adicionaram-se 4 mL de água régia, 1 mL de água e 1 mL de HCLO 4 , aquecendo-se por 30 min a 90 °C em chapa aquecedora, de acordo com uma modificação do procedimento de Akagi 17 .…”
Section: Metodologiaunclassified
“…Resultados obtidos por Hortellani et al 15 demonstraram que a contaminação por Hg dessa região estuarina pode ser avaliada pela normalização com o teor de Lama (silte + argila), utilizando dois procedimentos de normalização (extrapolação da curva de regressão e Fator de Enriquecimento).…”
Section: Normalização Dos Dadosunclassified